Inheritance of powdery mildew resistance and growth habit in fenugreek (Trigonella foenum-graecum L.) - Singh, R S Raje, D L Singhania, D (Journal of Spices and Aromatic Crops, 2003)
Inheritance of resistance to powdery mildew was studied by evaluating parents, F1 and F2 generations of cross UM-305 x UM-117 along with susceptible check varieties over the years for powdery mildew reaction. The F3 and F4 families of the cross were also evaluated along with the F1, parents and the check varieties for powdery mildew' reaction to confirm the results. X2 test was applied to test the fitness of assumed ratio. The inheritance pattern suggested resistance to powdery mildew was monogenic recessive. Results indicated that gene for powdery mildew resistance and gene for determinate growth habit assort independent of each other.